Personal Pronoun Translational Shifts in Anime Translations - Hasna, H H; Ali, M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the shift in personal pronoun terms found in anime translations. The data as the source text was taken from the anime kawaii dake ja nai shikimori san by Keigo Maki. The theory used in this study is the theory of intra system shifts by Catford (1965). The method used is descriptive qualitative method with note-taking technique. The results of this study indicate that the personal pronouns found in source language are anta, boku, watashi, ore, orera, omae,omaera, kimi, koitsu, kono yarou, etc. And in target language it becomes kamu, aku, kalian, and dia. As a conclusion, in SL there are various kinds of personal pronouns that are pronounced based on gender, while in TL they are neutral regardless of gender.